Teatro do oprimido na casa lar: processos educativos decorrentes - Alves, Thales Felipe Dantas (2024)
The Theatre of the Oppressed (TO), formulated by Augusto Boal, is symbolized by a tree whose roots must be planted in the soil of ethics and solidarity, allowing us to affirm that its foundation is the ongoing struggle against injustice, colonialism, and imperialism. Thus, this research aimed to describe, analyze, and understand the educational processes emerging from the social practice of TO, with a group of fifteen children and adolescents who were removed from their family environment and are in a foster care situation at the Casa Lar institution, under judicial determination, in the northern zone of São Paulo city. The insertion into the Casa Lar space occurred through workshops held on Saturday mornings, with an average duration of 50 minutes to 1 hour and 30 minutes, during the months of October 2022 to June 2023. Over thirteen meetings, exercises and games that comprise the TO method were developed. We used a descriptive qualitative research methodology, and the data collection method adopted was Field Diary, recording the activities, the participation of children and adolescents, as well as their speeches, gestures, expressions, sensations, and silences. The procedure adopted for data analysis was guided by Content Analysis, through which we found the units of context that enabled the creation of two categories: a) "Identifying the oppressors and the oppressed", and b) "Demechanizing the Bodies." From the analysis of the categories, it was possible to perceive that the workshops could significantly contribute to the children and adolescents recognizing the relationships of domination and oppression existing in the daily lives of their own lives, as well as identifying the possible oppressors surrounding them/us.